Makna Mabebasan Geguritan Bima Suarga Dalam Perspektif Panca Sradha - Subrata, I Nyoman; Sudarma, I Putu; Toya Wisuda, Pande Putu (Jurnal Penelitian Agama Hindu, 2024)
Entering the current era of digitalization, the Balinese Hindu community still adheres to local wisdom values, including the moral, social, philosophy (tatwa) and religious values ​​contained in geguritan (religious song) Bima Suarga. This research aims to examine the meaning of Geguritan Bima Suarga in Panca Sradha perspective. Research data was obtained through document study by analyzing the Geguritan Bima Suarga text, observations and interviews with members of the group (sekaa) santhi “Gangga Lingga Suara" and "Arsa Khanti", West Denpasar which was determined using purposive sampling. The collected data was analyzed descriptively interpretatively by applying hermeneutic theory. The results of the research show that mabebasan of the Geguritan Bima Suarga activities contain aesthetic meaning, social meaning and religious meaning which are able to strengthen the five basic beliefs (Panca Sradha) of Balinese Hindus, including: belief in the omnipotence of Hyang Widhi Wasa, belief in the existence of atma, karma phala, punarbhawa, and moksa, namely the union of the atma with paramatma (God) as a place of eternal happiness.